On Gatekeepers and Structural Competition Problems - Christian Rusche; Jan Büchel (Intereconomics, 2021)
The Digital Age saw the rise of several rapidly growing digital platforms with substantial market shares, and this development is expected to continue. Europe is a large target market for these globally operating platforms, although the majority of the most successful platforms come from the USA and Asia and will likely continue to do so in the future. This article reveals the reasons for the success of digital platforms and discusses the recent European Commission proposal for a Digital Markets Act based on the analysis of the status quo.
Keywords: 330; Digitale Medien; Erfolgsfaktor